Development and validation of COVID‐19 associated candidemia score (CAC‐Score) in ICU patients. Issue 2 (26th September 2022) - Kayaaslan, Bircan; Eser, Fatma; Asilturk, Dilek; Oktay, Zeynep; Hasanoglu, Imran; Kalem, Ayşe Kaya; Dönertaş, Gülen; Kaplan, Betul; Ozkocak Turan, Isıl; Erdem, Deniz; Bektas, Hesna; Guner, Rahmet
Abstract: Background: The development of candidemia is a highly fatal condition in severe COVID‐19 infection. Objectives: This study aimed to develop a candidemia prediction score in COVID‐19 patient based on the patient's clinical characteristics, and healthcare‐related factors during intensive care units (ICU) follow‐up. Patients/Methods: Severe COVID‐19 patients hospitalised in ICU in Ankara City Hospital during the one‐year period (August 15, 2020, and August 15, 2021) were included. After univariate analysis, multivariate analysis was applied using variable selection approach to investigate the effects of variables together and to create a score model for candidemia. Statistically significant factors were included in the development process of candida prediction score. Results: Of 1305 COVID‐19 ICU patients, 139 had a candidemia episode. According to the final model, four variables, presence of central venous catheter (CVC) (OR 19.07, CI 8.12–44.8, p  < .0001), multifocal colonisation (OR 2.28, CI 1.39–3.72, p 0.001), length of ICU stays ≥14 days (OR 3.62, CI 2.42–5.44, p  < .0001) and corticosteroids (OR 0.51, CI 0.34–0.76, p 0.0011) were the only statistically significant independent risk factors for candidemia. Score model was demonstrated by a nomogram, and the risk for candidemia was calculated to be high in patients who scored ≥56 points by using the criteria [CVC = 51, multifocal colonisation = 14, prolonged hospitalisation = 23, no steroid use = 12 points]. The AUC of the score is 0.84 (CI 0.81–0.87). Conclusion: We developed and validated an easy‐to‐use clinical prediction score for candidemia in severe COVID‐19 infection. In COVID‐19 ICU patients, the risk of candidemia is high if one of the other risk factors is present together with CVC.